Microcrack initiation mechanism of a duplex stainless steel under very high cycle fatigue loading condition: The significance of load partitioning and micro residual stresses. (15th October 2020) - Fu, Hongwang; Dönges, Benjamin; Krupp, Ulrich; Pietsch, Ullrich; Fritzen, Claus-Peter; Yun, Xinbing; Christ, Hans-Jürgen
Abstract: Investigation on the cyclic response of metallic materials in very high cycle fatigue (VHCF) is a challenging problem, which hinders the development of fatigue theories. To overcome this difficulty, we initially applied several sensible techniques, e.g., High-energy X-ray diffraction (HEXRD), confocal laser scanning microscope (CLSM), nanoindentation and transmission electron microscope (TEM) to investigate the cyclic response of a duplex stainless steel (DSS) in the VHCF regime. In-situ XRD and in-situ digital image correlation (DIC) experiments were subsequently performed at observed changing stages, intending to explore the underlying mechanism of microcrack initiation. The first-hand results obtained revealed that the austenite phase exhibits cyclic softening-hardening-softening behavior during the VHCF process. The in-situ investigations performed at the cyclic softening and hardening stages showed a load partitioning and a load transfer between the two phases, implying the cyclic response can significantly affect the distribution of the applied load. Residual strain obtained by DIC technique after unloading exhibited strong variations at phase boundaries, suggesting micro residual stresses have developed pronouncedly. Based on all the experimental findings, a unified crack initiation mechanism for the investigated DSS during VHCF loading was proposed. Graphical abstract: Image, graphical abstract